Current Issues of Information Disclosure in Integrated Reporting of Economic Entities - Olga S. Karpova; Irina A. Dymova (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки)
Domestic integrated reporting combines various types of reports generated by economic entities in order to improve the quality of information, develop integrated thinking, and create long-time values. The article introduces a new approach to the composition and content of integrated reporting. The research revealed some problems regarding the application of legislative norms in the field of classification and generalization of analytical, financial, and non-financial data. The authors analyzed the integrated reports available in the library of corporate non-financial reports of the Russian Union of Industrialists and Entrepreneurs. The analysis made it possible to summarize the presentation sequence of integrated reporting by Russian economic entities and its total share in the industry affiliation. The integrated reporting structure included eight elements with their specified names, content, and issues. Further research may improve the process of integrating financial and non-financial information into a single format. Integrated reporting can become an effective synthesis tool for organizing certain disparate parts into a single entity.